African Immigrant and Refugee Families’ Perceptions on Informational Support and Health Status: A Comparison of African Immigrants Living in South Africa and the United States (African Human Mobility Review, 2021)
The relationship between migration and health is complex, and its impact variesconsiderably among individuals, across migrant groups, and from country tocountry. Although African immigration to the United States (U.S.) and SouthAfrica has increased rapidly over the past two decades, little is known about thehealth experiences of this growing population even though conditionssurrounding the migration process have been found to increase vulnerability toill health. The aim of this study is to examine and compare the perceptions ofAfrican refugees and immigrants to South Africa and the U.S. on informationalsupport and its impact on health status. Data was collected from purposivelyselected 62 African immigrants to the United States and 66 African immigrantsto South Africa using the PROMIS Global Health v1.2 and the PROMIS Item Bankv2.0 (informational support) instruments which assess an individual’s generalphysical, mental and social health.